Nanopartículas e terapia fotodinâmica no tratamento de sementes de trigo - Duarte, Lucas Couto (2022)
The advance of wheat (Triticum spp.) in the brazilian cerrado demonstrates the impor-tance of the crop, evidencing the importance of using pathogen-free seeds. Nano-technology and photodynamic therapy emerge as a technological innovation in the control of plant diseases. The present work aimed to evaluate the efficacy of nanopar-ticles and photodynamic therapy in inhibiting the growth of Alternaria alternata in vitro and the treatment of wheat seeds, on the physiological and sanitary quality of the seeds. The phytosanitary test performed verified the presence of many fungi that infect the seeds, but only Alternaria alternata was found at sufficient incidence levels for an effective evaluation for the proposed seed treatment to determine the efficiency of the nanoparticles (ZnOCl; ZnOCl 1Cu; ZnOCl 0.1Ag; ZnO 1Cu; ZnO; ZnO 1Ag) and dyes (methylene blue and toluidine blue) in the inhibition of mycelial growth of Alternaria alternata in vitro. A. alternata mycelium discs, from naturally infested seeds, were multiplied in Petri dishes containing PDA medium and later transferred to Petri dishes with their respective treatments. To measure the efficiency of the nanoparticles applied directly to the seeds, they were treated with their respective nanoparticles, at concen-trations of 2.5 and 5 mg mL, carboxin + thi-ram and saline water (NaCl 0.45%). In photodynamic therapy the seeds were treated with toluidine blue, methylene blue and their combination, at concentrations of 50 and 100 µmol L-1 and irradiated with LED light, carboxin + thiram and saline water. The physiological aspects evaluated were germination, emergence, IVG, IVE, accelerated aging and strong normal seedlings, and seed health. In all physiological tests 400 wheat seeds were used per treatment and 200 seeds in the sanity test. The same treatments for both nanoparticles and photodynamic therapy were performed in vitro to measure the inhibition of mycelial growth of A. alternata. The use of ZnO:1Ag nanoparticles and photodynamic therapy with the com-bination of toluidine blue + 100 µmol L-1 methylene blue dye were efficient in inhibi-ting the mycelial growth of Alternaria alternata in vitro. The treatments with nanopar-ticles and photodynamic therapy showed no toxicity to the wheat seeds, not negatively affecting the physiological quality of the seeds. Photodynamic therapy and nanoparti-cles have shown enormous potential for use in controlling pathogens in seeds.